Drafted Leadership Theories; Modern And Islamic Perspectives Sources, Stand-Points And Leadership Spatialization On Educational Institution - Mulyadi, Mulyadi (LPPM Sekolah Tinggi Agama Islam Al Azhar, 2019)
Actually, in my sense, this paper theme was a difficult thing to be constructed. Because, the term of leadership was a huge discourse and still studied until this contemporary era. In other side, the shift of leadership study that far away from; collective evidence of leaders (in mean-stream) to personality and individual subjectivity; from common condition to situations were faced; and braches of method-theoretical framework were used, contributed the difficulties to write this paper more simply. So that, the paper will be focused, steered, and discussed three aspects of leadership studies: firstly, sources of leadership style and model based on scientific tradition (modern) or Islamic tradition. Secondly, the stand-point that contributes to frame leadership type. Thirdly, spatialization based on spatial theory what they call for leadership in educational administration or management studies. In the last, may this paper will give a new paradigm, how to frame and explain what leadership is, without bringing the normative perspective from religious life, because the leadership was a universal value that can arise from every human being, every place, and every situation based on the challenges face and the treat and solved them.